The shifting politics of foreign aid - Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2007)
Aid for good governance is much in the news. Wealthy countries promised dramatically to increase aid to the world's poorest countries at the G8 meeting in Gleneagles in 2005, agreeing to double aid for Africa by 2010 and noted that according to the OECD, aid for all developing countries would increase by around 50 billion per year by 2010 (Gleneagles G8 Communique, 8 July 2005 at www.g8.gov.uk). Promoting good governance is at the heart of these new commitments. To quote the G8 in 2007: "Good governance in Africa is vital to peace, stability, sustainable development, and growth. Without good governance, all other reforms will have limited impacts" (Heiligendamm G8 Communique, 8 June 2007 at www.g7.utoronto.ca). The promises being made by wealthy countries need to be set in a broader context. After 9/11 the global security agenda shifted. Suddenly the top priority was the War on Terror in Afghanistan and Pakistan - in fact, anywhere, where extremists might be contributing to international terrorist activities. Soon after, the invasion of Iraq signalled a new approach to containing and disarming states thought to have weapons of mass destruction (WMD). Inevitably demoted were efforts to prevent or resolve conflicts within poorer states, such as the one currently raging in the Darfur region of Sudan. These developments magnified three existing challenges to foreign aid. First, donors may hijack foreign aid to pursue their own security goals instead of helping the world's poor. Second, the wars in Afghanistan and Iraq and the broader War on Terror have been extremely costly, diverting aid and reducing other aid budgets. Generous promises of increased aid have not translated into real new flows. "Aid to Sub-Saharan Africa has stalled" concluded the OECD DAC in 2006 (OECD DAC 2006, Figure 2.2) while the World Bank report that net ODA disbursements in fact declined by US3 billion in 2006 (World Bank 2007, p.55). The third challenge to aid is that major donors are failing to coordinate aid through existing multilateral institutions, choosing instead to create their own new mechanisms and pursue their own priorities. The result is competition and clashes among priorities, creating aid chaos in many of the poorest recipient countries with regard to how aid is being delivered. This chapter assesses the scope for more aid and good governance promotion in the context of the emerging aid policies of the United States, Japan, the United Kingdom and the European Union.
Keywords: 330